Histamine containing endocrine cells in the human stomach. Issue 4 (April 1990) - Lönroth, H; Håkanson, R; Lundell, L; Sundler, F
Abstract : Histamine and chromogranin A-immunoreactive cells were studied in the mucosa of the human stomach. Cells reacting to both histamine and chromogranin A-antibodies (histamine containing endocrine cells), were demonstrated by double immunostaining and found to be restricted to the oxyntic mucosa. Histamine containing cells that did not stain with chromogranin A-antibodies were numerous throughout the stomach. Of the histamine immunoreactive cells in the oxyntic gland area 22% reacted with antibodies against chromogranin A. Histamine containing endocrine cells constituted 44% of the total number of endocrine cells in the oxyntic mucosa. These findings suggest that the histamine containing endocrine cells in the human stomach are identical with the so called enterochromaffin like cells.